ANALISIS PERAN PEMERINTAH DAERAH DALAM PELAKSANAAN PENGELOLAAN DAERAH IRIGASI DI KABUPATEN CILACAP TAHUN 2024 - Livia Eka Putri Febrianti; Rina Martini (Journal of Politic and Government Studies, 2026)
Cilacap Regency is one of the regions contributing to food security in Central Java Province and possesses a significant number of irrigation areas; this necessitates an optimal role for the local government in the management of these irrigation areas. This study aims to analyze the role of the Cilacap Regency local government in the management of irrigation areas in Cilacap Regency in 2024. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews with relevant agencies, namely the Cilacap Regency Water Resources Management Agency (PSDA) and the Cilacap Regency Agriculture Agency, as well as beneficiaries of the irrigation area specifically the Water User Farmers’ Association (P3A)—and were supplemented by documentary data and literature reviews. Analysis was conducted using Labolo’s (2014) theory of government roles, supplemented by an analysis based on the principles of good governance according to the UNDP as outlined by Sedarmayanti (2009). The research findings indicate that the Cilacap Regency Government has fulfilled its role as a regulator by enacting a number of regulations, while also serving as a provider of facilities and encouraging the active participation of water-user farmers through outreach activities. However, its role as a provider of facilities has not been fully realized due to budget constraints, resulting in 55% of the irrigation networks under the jurisdiction of Cilacap Regency being in poor condition. From a good governance perspective, irrigation management in Cilacap Regency has been participatory, equitable, and guided by applicable regulations, with supporting factors including a strong regulatory foundation, consistent routine inspection programs, and active participation by water-user farmers, while the main constraining factor is budget constraints.